Tourism Development and Local Communities: - Heredge, Marianne (Economic Journal of Nepal, 2005)
The goal of tourism in Nepal should be to improve the living standards of the people. In practice, the benefits from tourism are concentrated in the hands of a few people, typically based in Kathmandu. Small-scale, alternative forms of tourism could be developed to help to spread the economic benefits of tourism to local communities. A study of tourism in Upper Mustang was made in 2003 (Heredge, 2003) examining key issues in planning tourism development to maximize benefits to local communities there. In Upper Mustang at the time of writing, there was no evidence that any of the local people benefit economically from the limited numbers of visitors who go there. In Ladakh, an area in India that is also popular with tourists for trekking, a number of initiatives have helped to spread the economic benefits of tourism more widely to the villages and more remote areas in the region. Economic Journal of Nepal Vol.28(4) 2005 pp.205-214